2009
DOI: 10.1542/peds.2008-2379
|View full text |Cite
|
Sign up to set email alerts
|

Who Will Speak for Me? Improving End-of-Life Decision-Making for Adolescents With HIV and Their Families

Abstract: Family-centered advance care planning by trained facilitators increased congruence in adolescent/surrogate preferences for end-of-life care, decreased decisional conflict, and enhanced communication quality. Families acknowledged a life-threatening condition and were willing to initiate end-of-life conversations when their adolescents were medically stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
142
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(160 citation statements)
references
References 34 publications
4
142
0
7
Order By: Relevance
“…3,18,19 To date, most research evaluating pediatric palliative care has focused on adolescents who have HIV and cancer. [20][21][22] The current study examined, among a broad range of children who have chronic illness, the experiences that their parents and caregivers have had with ADs. This study aimed to identify knowledge and preferences about ADs and characteristics associated with interest in creating ADs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,18,19 To date, most research evaluating pediatric palliative care has focused on adolescents who have HIV and cancer. [20][21][22] The current study examined, among a broad range of children who have chronic illness, the experiences that their parents and caregivers have had with ADs. This study aimed to identify knowledge and preferences about ADs and characteristics associated with interest in creating ADs.…”
Section: Discussionmentioning
confidence: 99%
“…This can potentially eliminate some of the barriers to these conversations, such as provider time constraints and discomfort. 9,11,20,21 Limitations Our study has a number of limitations. The survey used in this study was developed specifically for this study and therefore not previously validated.…”
Section: (68)mentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary findings were that pACP can be implemented and was perceived as helpful. A randomised controlled trial specific to HIV-infected adolescents5 showed pACP to trigger positive emotional experiences in young people and their carers with less negative reactions when compared with those in the study's control arm not receiving pACP, also a better communication experience and marginally improved certainty about decisions in the intervention group 5 7. A subsequent randomised controlled trial of family centered pACP in young people with cancer concluded that those receiving pACP were significantly better informed about end-of-life decisions and the young people were more likely to allow family members to ‘do what is best at the time’ (100%) compared with the control group who did not receive pACP (62%) 6.…”
Section: What Is the Evidence To Support Advance Care Planning In Paementioning
confidence: 99%
“…[3][4][5] Although some provider and parent discomfort exists surrounding discussions of death and EoL care, [6][7][8][9] AYAs have expressed a desire and the ability to share their values, beliefs, and preferences for treatment at the EoL. [10][11][12][13][14][15][16][17] Moreover, the American Academy of Pediatrics, the Institute of Medicine, and the World Health Organization recommend involving AYAs in care decisions as much as possible, as they are developmentally and emotionally ready. 5,18,19 During normal adolescent development, individuals gain independence, formulate their self-identity, strengthen peer and romantic relationships, and define their future role in life.…”
Section: Discussionmentioning
confidence: 99%